Source-to-sink redistribution of critical elements from a granite–bauxite provenance in the fluvial peat system of Tayan Peatland, West Kalimantan: An analogue model for critical element enrichment in coals - Ferian Anggara; Mochamad Fachruddin Yusra; Salman Al Farizi; Yunanto Budi Prasetyo; Aldian Fahrialam; Esti Handini; Yan Restu Freski; Himawan Tri Bayu Murti Petrus; Tim A. Moore; Aulia Agus Patria (International Journal of Coal Geology, 2026)

Organic petrological and geochemical controls on critical element distribution in peat influenced by rhyolitic basement rocks from the Sebangau Peatland, Central Kalimantan: An analogue model for critical element enrichment in coals - Ferian Anggara; Shifeng Dai; Tim A. Moore; Auvanda Ivan Muhammad; Ofentse M. Moroeng; Jingjing Liu; Aldian Fahrialam; Himawan Tri Bayu Murti Petrus; Aulia Agus Patria (International Journal of Coal Geology, 2026)

Coal bed gas in Colombia: Current status - Jorge Eliecer Mariño-Martinez; Tim A. Moore; Juan Sebastian Gomez-Neita (International Journal of Coal Geology, 2026)

Biomarkers and organic carbon isotopes in Pennsylvanian–Early Permian coals of the Ordos Basin: Implications for palaeoenvironmental evolution in North China - Yang Liang; Wei Yuan; Jingjing Liu; Victor P. Nechaev; Tim A. Moore; Shaowei Zhang; Qian Wang; Jintian Zheng; Xiaoyun Yan; Mengda Yao; Shuai Kang; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Petrological, mineralogical, and geochemical compositions of the Eocene coals from Senakin Peninsula, South Kalimantan, Indonesia - Ferian Anggara; Donatus Hendra Amijaya; Tim A. Moore; Azmii Nanda Fadhillah; Aulia Agus Patria (International Journal of Coal Geology, 2025)

Isotopic and petrographic implications for fire type, temperature and formation of degradosemifusinite in fusain layers from an Early Cretaceous coal bed, Hailar Basin, Inner Mongolia, China - Ofentse M. Moroeng; Tim A. Moore; Jian Shen; Joan S. Esterle; Jingjing Liu (Fuel, 2025)

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Peatland Fungal Community Responses to Nutrient Enrichment: A Story Beyond Nitrogen - Meng Wang; Louis J. Lamit; Erik A. Lilleskov; Nathan Basiliko; Tim R. Moore; Jill L. Bubier; Galen Guo; Sari Juutinen; Tuula Larmola (Global Change Biology, 2024)
Anthropogenically elevated inputs of nitrogen (N), phosphorus (P), and potassium (K) can affect the carbon (C) budget of nutrient‐poor peatlands. Fungi are intimately tied to peatland C budgets due to their roles in organic matter decomposition and symbioses with primary producers; however, the influence of fertilization on peatland fungal composition and diversity remains unclear. Here, we examined the effect of fertilization over 10 years on fungal diversity, composition, and functional guilds along an acrotelm (10–20 cm), mesotelm (30–40 cm), and catotelm (60–70 cm) depth gradient at the Mer Bleue bog, Canada. Simultaneous N and PK additions decreased the relative abundance of ericoid mycorrhizal fungi and increased ectomycorrhizal fungi and lignocellulose‐degrading fungi. Fertilization effects were not more pronounced in the acrotelm relative to the catotelm, nor was there a shift toward nitrophilic taxa after N addition. The direct effect of fertilization significantly decreased the abundance of Sphagnum ‐associated fungi, primarily owing to the overarching role of limiting nutrients rather than a decline in Sphagnum cover. Increased nutrient loading may threaten peatland C stocks if lignocellulose‐degrading fungi become abundant and accelerate decomposition of recalcitrant organic matter. Additionally, future changes in plant communities, strong water table fluctuations, and peat subsidence after long‐term nutrient loading may also influence fungal functional guilds and depth‐dependencies of fungal community structure.

Fire activities and their impacts on local ecosystems in the southern Ordos Basin during the Middle Jurassic: Evidence from pyrogenic PAHs and petrography of inertinite-rich coal - Qiuchan Han; Jingjing Liu; James C. Hower; Tim A. Moore; Niande Shang; Shumao Zhao; Rongkun Jia; Shifeng Dai (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Constraints from lamprophyre petrogenesis on the timing of Eocene lithospheric thinning and associated rifting of Borneo and Sulawesi - David Murphy; Tim A. Moore; D. Hendra Amijaya; Ferian Anggara; Mike Friederich; Carmen Gaina; Jessica Trofimovs; Hayden Dalton; Edafe Ominigbo (Journal of Asian Earth Sciences, 2024)

Mechanistic simulations of kelp populations in a dynamic landscape of light, temperature, and winter storms - Tim M. Szewczyk; Pippa J. Moore; Dan A. Smale; Thomas Adams; Michael T. Burrows (Ecological Modelling, 2024)

Global Patterns of Metal and Other Element Enrichment in Bog and Fen Peatlands - Chetwynd Osborne; Spencer Gilbert-Parkes; Graeme Spiers; Louis James Lamit; Erik A. Lilleskov; Nathan Basiliko; Shaun Watmough; Roxanne Andersen; Rebekka E. Artz; Brian W. Benscoter; Luca Bragazza; Suzanna L. Bräuer; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Proceedings of the 38th Annual Conference of The Society for Organic Petrology: Organics in the geological cycle - Tim A. Moore; Carme Huguet; Ofentse M. Moroeng; Carol I. Sule (International Journal of Coal Geology, 2023)

Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Niche and neutral assembly mechanisms contribute to latitudinal diversity gradients in reef fishes - Nestor E. Bosch; Thomas Wernberg; Tim J. Langlois; Dan A. Smale; Pippa J. Moore; João N. Franco; Pierre Thiriet; Eric Feunteun; Cláudia Ribeiro; Pedro Neves; Rui Freitas; Karen Filbee‐Dexter; et al. (Journal of Biogeography, 2021)
Aim The influence of niche and neutral mechanisms on the assembly of ecological communities have long been debated. However, we still have a limited knowledge on their relative importance to explain patterns of diversity across latitudinal gradients (LDG). Here, we investigate the extent to which these ecological mechanisms contribute to the LDG of reef fishes. Location Eastern Atlantic Ocean. Taxon Reef‐associated ray‐finned fishes. Methods We combined abundance data across ~60° of latitude with functional trait data and phylogenetic trees. A null model approach was used to decouple the influence of taxonomic diversity (TD) on functional (FD) and phylogenetic (PD) diversity. Standardized effect sizes (SES FD and SES PD) were used to explore patterns of overdispersion, clustering and randomness. Information theoretic approaches were used to investigate the role of large‐ (temperature, geographic isolation, nitrate and net primary productivity) and local‐scale (human population and depth) drivers. We further assessed the role of demographic stochasticity and its interaction with species trophic identity and dispersal capacity. Results Taxonomic diversity peaked at ~15°–20°N, with a second mode of lower magnitude at ~45°N; a pattern that was predicted by temperature, geographic isolation and productivity. Tropical regions displayed a higher proportion of overdispersed assemblages, whilst clustering increased towards temperate regions. Phylogenetic and functional overdispersion were associated with warmer, productive and isolated regions. Demographic stochasticity also contributed largely to community assembly, independently of ecoregions, although variation was dependent on the trophic identity and body size of species. Main conclusions Niche‐based processes linking thermal and resource constraints to local coexistence mechanisms have contributed to the LDG in reef fishes. These processes do not act in isolation, stressing the importance of understanding interactions between deterministic and stochastic factors driving community structure in the face of rapid biodiversity change.

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Resources and geology of coalbed methane in China: a review - Yong Qin; Tim A. Moore; Jian Shen; Zhaobiao Yang; Yulin Shen; Geoff Wang (International Geology Review, 2018)

Can short-term litter-bag measurements predict long-term decomposition in northern forests? - Tim R. Moore; J. A. Trofymow; C. E. Prescott; B. D. Titus (Plant and Soil, 2017)

Nature and nurture in the dynamics of C, N and P during litter decomposition in Canadian forests - Tim R. Moore; J. A. Trofymow; Cindy E. Prescott; B. D. Titus (Plant and Soil, 2011)

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

Litter decomposition and nitrogen and phosphorus dynamics in peatlands and uplands over 12 years in central Canada - Tim R. Moore; J. A. Trofymow; M. Siltanen; L. M. Kozak (Oecologia, 2008)

Effects of nutrient addition on vegetation and carbon cycling in an ombrotrophic bog - JILL L. BUBIER; TIM R. MOORE; LESZEK A. BLEDZKI (Global Change Biology, 2007)
We measured net ecosystem CO 2 exchange (NEE), plant biomass and growth, species composition, peat microclimate, and litter decomposition in a fertilization experiment at Mer Bleue Bog, Ottawa, Ontario. The bog is located in the zone with the highest atmospheric nitrogen deposition for Canada, estimated at 0.8–1.2 g N m −2 yr −1 (wet deposition as NH 4 and NO 3 ). To establish the effect of nutrient addition on this ecosystem, we fertilized the bog with six treatments involving the application of 1.6–6 g N m −2 yr −1 (as NH 4 NO 3 ), with and without P and K, in triplicate 3 m × 3 m plots. The initial 5–6 years have shown a loss of first Sphagnum , then Polytrichum mosses, and an increase in vascular plant biomass and leaf area index. Analyses of NEE, measured in situ with climate‐controlled chambers, indicate that contrary to expectations, the treatments with the highest levels of nutrient addition showed lower rates of maximum NEE and gross photosynthesis, but little change in ecosystem respiration after 5 years. Although shrub biomass and leaf area increased in the high nutrient plots, loss of moss photosynthesis owing to nutrient toxicity, increased vascular plant shading and greater litter accumulation contributed to the lower levels of CO 2 uptake. Our study highlights the importance of long‐term experiments as we did not observe lower NEE until the fifth year of the experiment. However, this may be a transient response as the treatment plots continue to change. Higher levels of nutrients may cause changes in plant composition and productivity and decrease the ability of peatlands to sequester CO 2 from the atmosphere.

Locus heterogeneity in autosomal recessive congenital cataracts: linkage to 9q and germline HSF4 mutations - Tim Forshew; Colin A. Johnson; Shagufta Khaliq; Shanaz Pasha; Catherine Willis; Rashida Abbasi; Louise Tee; Ursula Smith; Richard C. Trembath; Syed Qasim Mehdi; Anthony T. Moore; Eamonn R. Maher (Human Genetics, 2005)

Urinary creatine profiles after administration of cell-specific testicular toxicants to the rat - Nigel P. Moore; Dianne M. Creasy; Tim J. B. Gray; John A. Timbrell (Archives of Toxicology, 1992)